The Effectiveness of the Talking Stick Method in Analyzing Report Text Information - Ghazali, Abdus Syukur; Suryantoro, Suryantoro; Zuhair, Ahmad Jauhari; Kusiah, Kusiah (Mindset : Jurnal Pemikiran Pendidikan dan Pembelajaran, 2025)
The ability to analyze information in report texts is an essential skill in strengthening students’ literacy in line with the Independent Curriculum. This Classroom Action Research (CAR) aims to examine the effectiveness of the Talking Stick method assisted by the Magic Bag learning media in improving the ability to analyze report texts in 29 students of class XI-F at SMP Negeri 10 Malang. This study is based on Vygotsky's Zone of Proximal Development (ZPD) theory and the principle of Culturally Responsive Teaching (CRT), which emphasizes the role of cultural context in learning. The research was conducted using the Kemmis & McTaggart model in two cycles. Local cultural content such as the Kasada Ceremony, Malang Tempo Doeloe, and Larung Sesaji Ceremony was integrated into collaborative learning activities. Data were collected through tests, observations, and questionnaires. The results showed a significant improvement in students' ability to analyze report texts, with the average score increasing from 62.5 in Cycle I to 78.2 in Cycle II, and the completeness percentage rising from 34.5% to 79.3% against the Minimum Completeness Criteria (KKM). Improvements were also seen in aspects such as identifying key information, understanding text structure, and drawing conclusions. This study demonstrates that the Talking Stick method combined with Magic Bag media and local cultural content effectively enhances students' literacy skills, encourages active participation, and strengthens contextual learning. It is recommended as an innovative cooperative strategy in teaching report texts at the junior high school level.